Something not so easy

Algebra Level 4

Let f ( x ) f(x) be a polynomial of degree 8 such that f ( r ) = 1 r f(r)=\dfrac {1}{r} for r = 1 , 2 , 3 , 8 , 9 r = 1,2,3, \cdots 8,9 .

What is 1 f ( 10 ) ? \dfrac{1}{f(10)}?


The answer is 5.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

3 solutions

Hugh Sir
Jul 2, 2019

Let g ( x ) = x f ( x ) 1 g(x) = xf(x)-1 .

Since f ( x ) f(x) is a 8th-degree polynomial, the degree of g ( x ) g(x) is 9.

Note that r f ( r ) 1 = 0 rf(r)-1 = 0 , for r = 1 , 2 , 3 , . . . , 8 , 9 r = 1,2,3,...,8,9 .

That is, x = 1 , 2 , 3 , . . . , 8 , 9 x = 1,2,3,...,8,9 are the roots of g ( x ) g(x) .

We can write g ( x ) g(x) as follows:

g ( x ) = A ( x 1 ) ( x 2 ) ( x 3 ) . . . ( x 8 ) ( x 9 ) = x f ( x ) 1 g(x) = A(x-1)(x-2)(x-3)...(x-8)(x-9) = xf(x)-1 , where A A is a real number.

If x = 0 x = 0 , we have g ( 0 ) = A ( 1 ) ( 2 ) ( 3 ) . . . ( 8 ) ( 9 ) = 0 f ( 0 ) 1 g(0) = A(-1)(-2)(-3)...(-8)(-9) = 0f(0)-1 .

That is, A = 1 9 ! A = \dfrac{1}{9!} .

If x = 10 x = 10 , we have g ( 10 ) = A ( 10 1 ) ( 10 2 ) ( 10 3 ) . . . ( 10 8 ) ( 10 9 ) = 10 f ( 10 ) 1 g(10) = A(10-1)(10-2)(10-3)...(10-8)(10-9) = 10f(10)-1 .

A ( 9 ! ) = 10 f ( 10 ) 1 A(9!) = 10f(10)-1

{ 1 9 ! } ( 9 ! ) = 10 f ( 10 ) 1 \{\dfrac{1}{9!}\}(9!) = 10f(10)-1

10 f ( 10 ) = 2 10f(10) = 2

Therefore, 1 f ( 10 ) = 10 2 = 5 \dfrac{1}{f(10)} = \dfrac{10}{2} = \boxed{5} .

Consider the product for positive integer r r :

P r = k = 1 , k r 9 ( x k ) = { 0 if k r ( 1 ) r 1 ( r 1 ) ! ( 9 r ) ! if x = r \displaystyle P_r = \prod_{k=1, k \ne r}^9 (x-k) = \begin{cases} 0 & \text{if }k \ne r \\ (-1)^{r-1}(r-1)!(9-r)! & \text{if }x=r \end{cases}

Note that P r P_r has a degree of 8. Therefore, f ( x ) f(x) can be expressed as:

f ( x ) = r = 1 9 ( 1 ) r 1 P r r ( r 1 ) ! ( 9 r ) ! = r = 1 9 ( 1 ) r 1 P r r ! ( 9 r ) ! = 1 9 ! r = 1 9 ( 1 ) r 1 ( 9 r ) P r \displaystyle f(x) = \sum_{r=1}^9 \frac {(-1)^{r-1}P_r}{r(r-1)!(9-r)!} = \sum_{r=1}^9 \frac {(-1)^{r-1}P_r}{r!(9-r)!} = \frac 1{9!} \sum_{r=1}^9 (-1)^{r-1}\binom 9r P_r

For integer x > 9 x > 9 , we can express P r = k = 1 9 ( x k ) x r P_r = \dfrac {\prod_{k=1}^9 (x-k)}{x-r} and f ( x ) f(x) as follows:

f ( x ) = 1 9 ! r = 1 9 ( 1 ) r 1 ( 9 r ) k = 1 9 ( x k ) x r = 1 9 ! r = 1 9 ( 1 ) r 1 ( 9 r ) ( x 1 ) ! ( x r ) ( x 10 ) ! = ( x 1 ) ! 9 ! ( x 10 ) ! r = 1 9 ( 1 ) r 1 ( 9 r ) x r \begin{aligned} f(x) & = \frac 1{9!} \sum_{r=1}^9 (-1)^{r-1}\binom 9r \frac {\prod_{k=1}^9 (x-k)}{x-r} \\ & = \frac 1{9!} \sum_{r=1}^9 \frac {(-1)^{r-1}\binom 9r(x-1)!}{(x-r)(x-10)!} \\ & = \frac {(x-1)!}{9!(x-10)!} \sum_{r=1}^9 \frac {(-1)^{r-1}\binom 9r}{x-r} \end{aligned}

Then we have:

f ( 10 ) = 9 ! 9 ! ( 0 ! ) r = 1 9 ( 1 ) r 1 ( 9 r ) 10 r Since ( n r ) = ( n n 1 ) = r = 1 9 ( 1 ) r 1 ( 9 9 r ) 1 + 9 r = r = 0 8 ( 1 ) r 1 ( 9 r ) r + 1 = r = 0 9 ( 1 ) r 1 ( 9 r ) r + 1 + 1 10 Note that ( 1 t ) n = k = 0 n ( n k ) t k = 0 1 ( 1 t ) 9 d t + 1 10 = ( 1 t ) 10 10 0 1 + 1 10 = 1 10 + 1 10 = 1 5 \begin{aligned} f(10) & = \frac {9!}{9!(0!)} \sum_{r=1}^9 \frac {(-1)^{r-1}\binom 9r}{10-r} & \small \color{#3D99F6} \text{Since }\binom nr = \binom n{n-1} \\ & = \sum_{r=1}^9 \frac {(-1)^{r-1}\binom 9{9-r}}{1+9-r} \\ & = \sum_{r=0}^8 \frac {(-1)^{r-1}\binom 9r}{r+1} \\ & = \sum_{r=0}^9 \frac {(-1)^{r-1}\binom 9r}{r+1} + \frac 1{10} & \small \color{#3D99F6} \text{Note that } (1-t)^n = \sum_{k=0}^n \binom nk t^k \\ & = \int_0^1 (1-t)^9 dt + \frac 1{10} \\ & = - \frac {(1-t)^{10}}{10} \bigg|_0^1 + \frac 1{10} \\ & = \frac 1{10} + \frac 1{10} = \frac 15 \end{aligned}

Therefore, 1 f ( 10 ) = 5 \dfrac 1{f(10)} = \boxed 5 .

Chris Lewis
Jul 2, 2019

One simple method is to construct and extend a difference table.

Another approach is to explicitly construct the polynomial.

Note that x f ( x ) 1 xf(x)-1 is a polynomial of degree 9 9 with roots at x = 1 , 2 , , 9 x=1,2,\ldots,9 . This means it must have the form k ( x 1 ) ( x 2 ) ( x 9 ) k(x-1)(x-2)\cdots (x-9) , where k k is a constant.

By comparing the constant terms, we can see that k = 1 9 ! k=\frac{1}{9!} . So f ( x ) = 1 9 ! x ( 9 ! + ( x 1 ) ( x 2 ) ( x 9 ) ) f(x)=\frac{1}{9!x} (9!+(x-1)(x-2)\cdots (x-9))

We want to find f ( 10 ) f(10) . This actually works out neatly, since ( 10 1 ) ( 10 2 ) ( 10 9 ) (10-1)(10-2)\cdots (10-9) is just 9 ! 9! .

Substituting in, we find f ( 10 ) = 1 5 f(10)=\frac{1}{5} so the required answer is 5 \boxed5 .

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...